2012
DOI: 10.1371/journal.pgen.1002518
|View full text |Cite
|
Sign up to set email alerts
|

Negative Supercoiling Creates Single-Stranded Patches of DNA That Are Substrates for AID–Mediated Mutagenesis

Abstract: Antibody diversification necessitates targeted mutation of regions within the immunoglobulin locus by activation-induced cytidine deaminase (AID). While AID is known to act on single-stranded DNA (ssDNA), the source, structure, and distribution of these substrates in vivo remain unclear. Using the technique of in situ bisulfite treatment, we characterized these substrates—which we found to be unique to actively transcribed genes—as short ssDNA regions, that are equally distributed on both DNA strands. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 65 publications
5
74
0
Order By: Relevance
“…DRIP analysis demonstrated that the expression of RNase HI reduced R‐loop formation in IGVL to near background levels (Fig 4C). However, it did not affect Ig diversification (Fig 4D), consistent with the observations of Martin and colleagues in hypermutating human B cells (Parsa et al , 2012). Thus, while H3.3 promotes the formation of R‐loops in IGVL, R‐loops are not necessary intermediates in AID‐dependent Ig diversification.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…DRIP analysis demonstrated that the expression of RNase HI reduced R‐loop formation in IGVL to near background levels (Fig 4C). However, it did not affect Ig diversification (Fig 4D), consistent with the observations of Martin and colleagues in hypermutating human B cells (Parsa et al , 2012). Thus, while H3.3 promotes the formation of R‐loops in IGVL, R‐loops are not necessary intermediates in AID‐dependent Ig diversification.…”
Section: Resultssupporting
confidence: 91%
“…Negative supercoiling creates localised denaturation bubbles (Jeon et al , 2010), which have been shown to provide an ideal substrate for AID on both strands of a plasmid, even in the absence of transcription (Shen & Storb, 2004; Shen et al , 2005). Transcription‐associated negative supercoiling has also been proposed to explain the short patches of AID and bisulphite‐accessible ssDNA observed in the Ig genes of hypermutating Ramos cells and stimulated murine primary B cells (Ronai et al , 2007; Parsa et al , 2012), which are similar to the patches of ssDNA we observe in the diversifying IGVL R of DT40 and, importantly, show are sensitive to the absence of H3.3.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…These DNA lesions are then converted into point mutations during SHM and into DNA double-stranded breaks (DSBs) during CSR or aberrant chromosomal translocations. AID shows selectivity and deaminates single-stranded DNA (ssDNA) or supercoiled DNA that creates single-stranded patches of DNA [9, 10], but does not deaminate double-stranded DNA (dsDNA) or DNA:RNA hybrids [11, 12]. During SHM, point mutations and sometimes insertions and deletions, are introduced at a very high rate into the recombined variable region exons encoding IgH and IgL, which in some instances will generate B cells with increased antigen affinity.…”
Section: Aid and Antibody Maturationmentioning
confidence: 99%